Teaching Children in Open Public Space: Tirto Agung Park - Rakhmatulloh, Anita Ratnasari; Kusumo Dewi, Diah Intan (2020, 2020)
Parks important venues for children to engage in active play, learn, exercise, recreation for children's development and skills training of cognitive, affective, and psychomotor. Teaching ethics in the park to the student is one of the ways to make the children care about the social environment. Children will meet other people in the park to interact and play with a new friend. In the park, children also use the facilities available. Teaching the ethic in the park will make students know what they should do in open public space. The purpose of this study is to provide education to students of Pedalangan Elementary School about the ethics in the park, which are expected to influence awareness to keep public open space clean and make them safe when playing in the park. This study uses qualitative methods with data collection methods in the form of observation. The results of this study are students' understanding of the ethics in the park increased like avoid strangers, keep the park clean, and keep politeness.